2015
DOI: 10.1007/s00394-015-0872-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inorganic nitrate and beetroot supplementation on endothelial function: a systematic review and meta-analysis

Abstract: Inorganic nitrate and beetroot supplementation was associated with beneficial effects on EF. These effects appear to be reduced in older subjects and in subjects with greater cardiometabolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 35 publications
1
85
0
4
Order By: Relevance
“…In recent previous reports by our group, two systematic reviews of the literature showed that inorganic nitrate or beetroot juice consumption were associated with significant reductions in SBP (-4.4mmHg 95% CI: -5.9, -2.8; P< 0.001) [3] , and improvements in FMD (SMD 0.52; 95 % CI 0.15, 0.68; P = 0.002) [4].…”
Section: Scientific Analysis Of Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…In recent previous reports by our group, two systematic reviews of the literature showed that inorganic nitrate or beetroot juice consumption were associated with significant reductions in SBP (-4.4mmHg 95% CI: -5.9, -2.8; P< 0.001) [3] , and improvements in FMD (SMD 0.52; 95 % CI 0.15, 0.68; P = 0.002) [4].…”
Section: Scientific Analysis Of Findingsmentioning
confidence: 74%
“…Recent systematic reviews of the literature indicate that supplementation with dietary nitrates, or foods rich in these compounds such as beetroot, have the potential to lower blood pressure [3] and improve endothelial function [4], both regarded as early indicators of cardiovascular diseases (CVD). These benefits are valuable when developing effective nutritional strategies targeting specific key metabolic risk factors for the prevention and management of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from .30, mostly small-scale randomized controlled trials have established that intake of nitrate-rich vegetables can enhance endogenous NO levels and improve measures of vascular health, including blood pressure and endothelial function (9)(10)(11)(12). There is a need to determine whether these improvements in risk factors can translate into improved long-term 4 Measured in 1215 participants.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that increased nitrate intake can reduce blood pressure (11) and improve endothelial function (12). It has not been determined, however, whether this action translates into a reduction in the long-term risk of ASVD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 4-week supplementation with sodium nitrate resulted in improved endothelial dysfunction when assessed by brachial artery flow mediated vasodilation and also reduce arterial stiffness in an elderly population [12]. A beneficial effect of inorganic nitrate or beetroot supplementation on endothelial function was reported by a recent meta-analysis [13]. Another recent meta-analysis (total number of participants n = 254; 7-30 participants per study) suggests that a dose of 300-600 mg of sodium nitrate modestly reduces blood pressure [14].…”
Section: Aimmentioning
confidence: 97%